Reconstructing diets of hunted sika deer from Torihama Shell Midden site (ca. 6,000 years ago) by dental microwear texture analysis - Sato, Koyo; Sato, Takao; Kubo, Mugino O. (Frontiers in Ecology and Evolution, 2022)
Sika deer (Cervus nippon) is the most abundant ruminant in the Japanese archipelago and has been the primary hunting target, including during the prehistoric ages. Abundant skeletal remains of sika deer have been excavated from archaeological sites of the Jomon periods (ca. 15,000–2,400 BP). We reconstructed the feeding habits of sika deer from the Torihama shell midden site in Fukui Prefecture, western Japan. The Torihama site is one of the most well-preserved archaeological sites of the Jomon period, and we investigated materials from the layers of the Early Jomon period (ca. 6,000 BP). In this study, we obtained three-dimensional tooth surface texture from the lower molars of excavated deer and measured microwear texture using international surface roughness parameters (ISO 25178-2) to infer their habitat use. Next, we estimated the percentage of grasses in the diet by using the reference dataset for extant sika deer with known diets. The results show that the Torihama deer overlapped with mixed feeding and grazing sika deer populations. Moreover, the proportion of grasses in the diet was estimated to be 50.7% on average but showed a wide range among the Torihama deer. This result implied that Torihama deer were mixed feeders of dicot leaves and grasses and had a flexible diet adapted to the vegetation of its habitat. Our results support the paleoenvironmental estimation that the Torihama shell midden site contained mixed vegetation of evergreen, deciduous, and coniferous trees around the Mikata Five Lakes in the Early Jomon period. These findings provide insights into the highly plastic diets of the extant sika deer in the Japanese archipelago.